Effects of unilateral training on rapid force production in athletes: a systematic review and meta-analysis - Zhuang, Y.; Zhang, Y.; Ma, L.; Han, J. (Frontiers in Physiology, 2026)
Introduction: Unilateral training has been increasingly applied in athletic conditioning; however, its effects on rate of force development (RFD) remain unclear. This study aimed to systematically evaluate the effects of unilateral training on RFD in athletes.